2014
DOI: 10.1111/ijcp.12514
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of prostate cancer risk and association with consumption of fish and fish-oils: analysis of 495,321 participants

Abstract: Introduction: Fish-oils have a potential role in inflammation, carcinogenesis inhibition and favourable cancer outcomes. There has been increasing interest in the relationship of diet with cancer incidence and mortality, especially for eicosapantaenoic acid (EPA) and docosahexaenoic acid (DHA). This systematic-analysis of the literature aims to review evidence for the roles of dietary-fish and fish-oil intake in prostate-cancer (PC) risk, aggressiveness and mortality. Methods: A systematicreview, following PRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 51 publications
1
20
0
1
Order By: Relevance
“…Furthermore, a genome-wide association study 20 identified 76 variants associated with a higher risk of developing prostate cancer, predominantly in populations of European descent compared to controls from studies in populations of European, African, Japanese, and Latin American descent. Since the association between lifestyle factors and prostate cancer risk is still unclear,21, 22, 23, 24, 25, 26, 27 to elucidate the pathogenesis of prostate cancer, the identification of genetic variants associated with prostate cancer risk among Japanese men is important.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a genome-wide association study 20 identified 76 variants associated with a higher risk of developing prostate cancer, predominantly in populations of European descent compared to controls from studies in populations of European, African, Japanese, and Latin American descent. Since the association between lifestyle factors and prostate cancer risk is still unclear,21, 22, 23, 24, 25, 26, 27 to elucidate the pathogenesis of prostate cancer, the identification of genetic variants associated with prostate cancer risk among Japanese men is important.…”
Section: Discussionmentioning
confidence: 99%
“…Omega-3 and omega-6 fatty acids act synergistically on tumor cell survival, proliferation and angiogenesis by increasing lipid peroxidation ( 63 ). However, these biological actions may not translate into clinical significance, and require confirmation in interventional trials or observational studies with a long follow-up duration ( 64 ).…”
Section: Evidence Synthesismentioning
confidence: 99%
“…A study on leukemia demonstrated that n ‐3 PUFAs could activate the RAS/ERK/C/EBPb pathway through induced phosphorylation . In prostate cancer, several epidemiologic studies reached different conclusions , leading to an unresolved debate over the effects of FO on prostate cancer risk . However, the majority of in vitro and in vivo studies showed that n ‐3 PUFAs exert inhibitory functions on prostate cancer growth.…”
Section: Introductionmentioning
confidence: 99%